Obstacles influencing The obstacles influencing sports activities in Saudi universities - SAMEER MOHAMMED SAYYD (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
Objectives: The aim of this study to evaluate the sports activities in Saudi universities from the students perspective also, to investigate the obstacles influencing sports activities in Saudi universities. Methods: This study is used the descriptive approach to study 114 respondents were randomly selected from in some Saudi university. The questionnaire was used study comprises five questions. An online questionnaire was designed by Google forms and was distributed by email and WhatsApp. Results: The study revealed some obstacles that hinder the success of sports activities in Saudi Arabia universities for males are: Sports injuries, Lack of facilities, Lack of tools, Non updated programs, admission conditions are not clear, Lack of student interest to do sport, Lack of time in university time table to do sport, There is no scheduled for the sport activities in Saudi universities, lack of fund and lack of human recourse. Conclusion: Can see the importance to investigate the most important factors to enhance sports activities. As well most of the university's students agree with the important need to enhance the sports activities. In addition, all of the obstacles consider by the student are easy to solve if universities implement important the factors.